Water and carbon risks within hydropower development on national scale. (1st November 2022) - Chen, Xiuzhi; Liu, Chang; van Oel, Pieter; Mergia Mekonnen, Mesfin; Thorp, Kelly R.; Yin, Tuo; Wang, Jinyan; Muhammad, Tahir; Li, Yunkai
Graphical abstract: Highlights: The positive and negative environmental benefits of hydropower are co-existed, and it cannot be ignored. This study firstly assessed environmental burden at national scale, including water footprint and carbon footprint. Machine learning offers a new approach: estimating environmental burden of hydropower with inadequate data. Hydropower replacing thermal power cannot achieve complete cleanliness. Abstract: The United Nations has proposed Sustainable Development Goals (SDGs), which aim to achieve coordinated green development in energy, economic and environmental dimensions. Hydropower is currently the world's most important renewable energy source, it has made up for the electricity shortage and created great economic value, but at the same time, the environmental impacts occurred cannot be ignored. However, current studies focused on a single or a few specific projects, it has not achieved quantitative environmental assessment on regional scale. To fill this gap, we selected China, the world's largest developing country, as the case for the first time to assess the hydropower water footprint (WF) and carbon footprint (CF) at both spatial and temporal dimensions. The results showed that total WF & CF of hydropower in China are 13.90 billion m 3 (closes to half annually runoff of the Yellow River) and 413.39 billion kg eqCO2 (is equivalent to burning 1.5 billion t of coal), with intensity of 53.95 m 3 /MWh and 125.89 kg eqCO2 /MWh respectively. The hydropower WF alone is more than regional available water occurred in 1/4 provinces of China. The emission reduction effect of hydropower is overestimated by 11.72 %, this should be considered in plans that hydropower replacing thermal power. Considering the CF of hydropower itself, 25–53 % of the regional carbon emission reduction target would not be achieved. From a global perspective, there about 1/3 countries' hydropower WF exceed 10 % of the water resource availability, and about 1/4 countries' hydropower CF exceeds 5 % of carbon emission.